Türkiye’nin kuruluş sürecinde meşrutiyet araçlarından biri olarak tiyatro - Akdeniz, Aylin (My University, 2005)
Bu çalışmada, Türkiye Cumhuriyeti'nin kuruluş süreci, uluslaşma projesi içinde ele alınmıştır. Sözü edilen projenin temel dayanakları, hem Türkiye Cumhuriyeti, hem de dünyadaki oluşumlar içinde değerlendirilmiştir. Uluslaşma projesi incelenirken, Cumhuriyet'in referansı olarak 'Batı', 'Batı' kavramı çözümlenirken de 'kapitalizm' üzerinde durulmuştur. Bu çerçevede Cumhuriyet'in kültür politikası ve bu bağlamda tiyatronun uluslaşma projesi kapsamında yüklendiği görevler irdelenmiştir. In this thesis, the founding process of Turkey is discussed within the construction of nation project. The mentioned projects' basic resources are examined on the scope of the formations both in the Turkish Republic and in the world. During the examination of the construction of nation project, 'West' by means of a reference for the Republic also while analyzing the 'West' notion 'capitalism' is being stressed. According to this framework, the cultural politics of the Republic and in this context the tasks that theatre undertook are being considered within the construction of nation project.
Keywords: Kültür; Kültür Politikası_Türkiye; Toplum bilimleri